2018
DOI: 10.2147/cmar.s181214
|View full text |Cite
|
Sign up to set email alerts
|

Transanal total mesorectal excision for low rectal cancer: a case-matched study comparing TaTME versus standard laparoscopic TME

Abstract: BackgroundTransanal total mesorectal excision (TaTME) is emerging as a novel alternative to laparoscopic total mesorectal excision (LaTME). The aim of this study was to compare clinical and pathological results from these two techniques in patients undergoing rectal resections because of low rectal cancer.Materials and methodsThirty-five patients undergoing TaTME were matched with 35 patients operated on using LaTME. Composite primary endpoint (complete TME, negative circumferential resection margin [pCRM], an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(54 citation statements)
references
References 48 publications
0
52
1
Order By: Relevance
“…), and that more than one‐third of all patients still had a stoma at the end of the study. One of the presumed advantages of TaTME is a reduced need for permanent stomas, but the findings in this national cohort do not support the method as a means of avoiding a stoma.…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…), and that more than one‐third of all patients still had a stoma at the end of the study. One of the presumed advantages of TaTME is a reduced need for permanent stomas, but the findings in this national cohort do not support the method as a means of avoiding a stoma.…”
Section: Discussioncontrasting
confidence: 72%
“…The transanal approach aims to increase visibility and give better access to the dissection planes, and thus to increase the quality of the resected specimen. TaTME should also offer a safer anastomotic technique by the use of a distal purse‐string suture, allowing a low anastomosis in patients who might otherwise need a permanent stoma. The indication for TaTME has currently been extended to include higher tumours and women.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…One thousand two hundred and forty-seven citations were retrieved from the search strategy. Finally, twelve studies [24][25][26][27][28][29][30][31][32][33][34][35] were included in the analysis, with a total of 899 patients (411 patients in TaTME group, 488 patients in LaTME group) ( Figure 1). The characteristics of eligible studies are shown in Table I.…”
Section: Resultsmentioning
confidence: 99%